A comprehensive meta-analysis of the relationship between Emotional Intelligence and health - Martins, A.; Ramalho, N.; Morin, E. (Personality and Individual Differences, 2010)
In everyday life, people have the notion that acknowledging and dealing effectively with emotions contributes to their wellbeing. A recent meta-analysis by Schutte, Malouff, Thorsteinsson, Bhullar, and Rooke (2007) indicated that Emotional Intelligence (EI) is associated with better health. Our purpose is to expand their work by including: (1) studies published after the date considered by them; (2) non-English studies; and (3) a cumulative meta-analysis to check for the sufficiency and stability in the history of this research domain. Based on 105 effect sizes and 19,815 participants, the results globally support previous findings. When measured as a trait, EI was more strongly associated with health (r?=34) than when it was measured as an ability (r?=17). The weighted average association with mental (r?=36) and psychosomatic health (r?=33) was higher, than the association with physical health (r?=27). Within the trait approach, the TEIQue showed the strongest association with mental health (r?=50), followed by the EQ-i (r?=44), SEIS (r?=29) and TMMS (r?=24). Furthermore, the cumulative meta-analysis indicated that this line of research has already reached sufficiency and stability. Overall, the results are encouraging regarding the value of EI as a plausible health predictor.